Viewing the Viewers: How Adults With Attentional Deficits Watch Educational Videos. (October 2014) - Hassner, Tal; Wolf, Lior; Lerner, Anat; Leitner, Yael
Objective: Knowing how adults with ADHD interact with prerecorded video lessons at home may provide a novel means of early screening and long-term monitoring for ADHD.Method: Viewing patterns of 484 students with known ADHD were compared with 484 age, gender, and academically matched controls chosen from 8, 699 non-ADHD students. Transcripts generated by their video playback software were analyzed using t tests and regression analysis.Results: ADHD students displayed significant tendencies ( p ≤ .05) to watch videos with more pauses and more reviews of previously watched parts. Other parameters showed similar tendencies. Regression analysis indicated that attentional deficits remained constant for age and gender but varied for learning experience.Conclusion: There were measurable and significant differences between the video-viewing habits of the ADHD and non-ADHD students. This provides a new perspective on how adults cope with attention deficits and suggests a novel means of early screening for ADHD.